EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995952 ZenodoArchiveConcept: 14995951 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7303773 10.53832/edtechhub.1101 2405685:RMJK6G6Q
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen